2010
DOI: 10.1111/j.1095-8312.2010.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in diet quality: antioxidants, invertebrates and blue tits Cyanistes caeruleus

Abstract: Breeding success is often dictated by the degree to which parents can synchronize the maximum food requirements of offspring to the peak in abundance of invertebrate prey. Less studied is how the nutritional quality of individual diet items impacts on breeding. In the present study, we assessed the abundance and antioxidant concentrations of arboreal arthropods from oak woodland and provisioning behaviour of the blue tit Cyanistes caeruleus. Dietary antioxidants are important during development because they de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 30 publications
3
66
0
5
Order By: Relevance
“…Along these lines, we have shown previously that to feed young with one or the other type of caterpillar is not a trivial matter from the point of view of the offspring . In this sense, recent studies (Arnold et al, 2010;Eeva et al, 2010) have shown that lepidopteran larvae can differ greatly in their concentration of carotenoids (antioxidants such as lutein, zeaxanthin, β-carotene). On the basis of their appearance and the birds' preference, it is likely that noctuids (caterpillars with a greater amount of tissue) possess a higher caloric content in comparison with tortricid larvae, whose aspect is less consistent (watery guts) and nutritive.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we have shown previously that to feed young with one or the other type of caterpillar is not a trivial matter from the point of view of the offspring . In this sense, recent studies (Arnold et al, 2010;Eeva et al, 2010) have shown that lepidopteran larvae can differ greatly in their concentration of carotenoids (antioxidants such as lutein, zeaxanthin, β-carotene). On the basis of their appearance and the birds' preference, it is likely that noctuids (caterpillars with a greater amount of tissue) possess a higher caloric content in comparison with tortricid larvae, whose aspect is less consistent (watery guts) and nutritive.…”
Section: Discussionmentioning
confidence: 99%
“…Lepidoptera larvae differ greatly in their size, shape, mobility (Gómez de Aizpurúa 2003) and carotenoid level (Isaksson and Andersson 2007;Arnold et al 2010) and, consequently, the fact that birds feed their young with one or another species is not trivial. We have shown that diet features seem to have an effect on nestling condition, which is a critical determinant of post-fledging survival (Greño et al 2008) and recruitment rate (Both et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Females that lay smaller clutches may have lower intrinsic quality or they may breed in poorer-quality territories and thus they may be exposed to lower food availability, insufficient for laying more eggs in a clutch (Minot 1981, Perrins andMcCleery 1989). Female Great Tits consume high numbers of caterpillars during the breeding period (Török 1986), which are rich in dietary antioxidants (Arnold et al 2010, Eeva et al 2010. We may thus assume that females with a lower availability of antioxidant-rich food laid smaller clutches and possibly also possessed a less efficient antioxidant capacity during the laying period.…”
Section: Eggshell Spotting and Female Traitsmentioning
confidence: 99%